Analisis Posisi Hukum Anak dalam Sistem Pemidanaan Terkait Tindak Pidana Narkotika - Indah Nadya Anggreni; Murjani Murjani; Nurul Shobah (Departement of Mathematics Education, 2023)
This research investigates and analyzes the legal position of children within the framework of the criminal justice system concerning narcotics offenses, with a specific focus on the diversion mechanism. Diversion serves as the primary focus to explore how the current legal system responds to children's involvement in narcotics cases, as well as the effectiveness and role of diversion in protecting and rehabilitating involved children. The study encompasses an in-depth examination of the legal regulations governing the protection, rehabilitation, and law enforcement concerning children involved in cases of drug abuse.